Perbandingan Hasil Pemeriksaan Glukosa Darah Dengan Menggunakan Serum Dan Plasma Natrium Fluorida (NaF) Di Laboratorium Klinik Medika Jayapura - Herlando Sinaga; Cuti Irianti (Universitas Muhammadiyah Surabaya, 2020)
The purpose of this research was to compare the results of examination of blood glucose levels using serum and plasma Sodium Fluoride (NaF). The population used in this study were all patients who came to check blood glucose while at the Medika Clinic Laboratory. The number of samples in this research was 67 (total population). The method used in examination of blood glucose is the enzymatic method of Glucose Oxidase (GOD - PAP). This research was conducted for 1 month, from April 1 to April 30, 2017. To compare the values between serum and plasma sodium fluoride (NaF) specimens, it was analyzed statistically using the Social Science Stastistial Program (SPSS) for windows version 21 with the test method Mann Whitney and obtained a mean of 154.49 mg/dl in serum specimens and 145.36 mg/dl in plasma specimens of sodium fluoride (NaF). The results of statistical tests of blood glucose levels with serum and plasma NaF specimens showed no significant difference and obtained a significance value of 0.196 which means a probability >0.05. The conclusion of this research is that there is no significant difference between the examination of blood glucose using serum specimens and plasma Sodium Fluoride (NaF).Keywords : Blood Glucose, Serum, Sodium fluorida (NaF)